The chocolate factory ghost - "Connell, O David" (Bloomsbury Children's Books: London, 2018)
Archie McBudge knows his lucky underpants must really work because when he and his mum are summoned to Honeystone Hall in the remote Scottish village of Dundoodle, they find Archie has inherited not only the enormous hall, but the whole of the world-famous McBudge Confectionery Company from Great-Uncle Archibald. That's a new home, a fortune and a lifetime's supply of treats rolled into one! But all is not well in Dundoodle, and when Archie reads the mysterious letter his great-uncle left him he finds himself on a quest to save his family's company from ruin. With the help of his new friends Fliss and Billy, Archie has to try to figure out the puzzles of Honeystone before his sweet future melts away like an ice lolly in the sun! Fans of How to Train Your Dragon and Tilly and the Time Machine will be hungry for this delicious mystery full of weird clues, strange creatures, malevolent relatives and lots and lots of sweets!
Keywords: Detective and mystery fiction